Teologi-Estetis Tari Daha Malom Kajian Filsafat Agama Hindu - Putu Sri Marselinawati; Ni Wayan Juli Artiningsih (Jnanasidanta, 2021)
Art is a very important component in the implementation of the yadnya ceremony, especially in Bali, without art the yadnya ceremony will feel meaningless. Daha Malom dance is a sacred dance created expressively to express the omnipotent nature of God giving salvation as a complement to ritual ceremonies at Puseh Temple, Ngis Karangasem Village. In the creation of this sacred symbol, three important elements are inseparable, namely satyam (truth), siwam (holiness) and sundaram (beauty). Daha Malom Dance in Ngis Village is an oral tradition which is the appreciation of the local community with environmental conditions, until now the truth is still believed, this method of proving the truth through oral tradition is in line with the way of proving the truth of Mimamsa Darsana. Respect for nature is one of the implementations of the Sankhya-darsana teachings which aim to remind humans of their origin, as an identity that comes from God, the harmony of Bhuana Agung and Bhuana Alit which is expressed in the Daha Malom Dance reflecting the sradha and devotion of Hindus in Ngis Karangasem Village. This study used qualitative research methods. Qualitative research is research that uses data that is stated verbally and qualifications are theoretical